Pengaruh Kualitas Layanan terhadap Kepuasan Konsumen pada Rumah Makan Bujang - Harly Hakubun; Djoko Wijono (Universitas Proklamasi 45 Yogyakarta, 2014)
This study aimed to examine the influence of service quality to customer satisfaction in RM Bujang. The sample in this study is the customer who ever ate at RM Bujang. Samples were collected by using a accidental sampling. There are 150 responder which have been fulfilling the conditions needed. The analytical method used is multiple regression analysis. The result of the study showed that service quality consists of tangibles, reliability, responsiveness, assurance, and emphaty effect on customer satisfaction. The result of multiple regression analysis showed that variable the reliability and emphaty has a coefficient of 0.710 and 0.922. The result of the study showed that service quality consist of tangibles, reliability, responsiveness, assurance, and emphaty to customer satisfaction has given Adjusted R Square of 0,474 0r 47,3%.